(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Every nation has proverbs with the concepts of "wealth" and "poverty". In this article, with the help of folk proverbs and sayings, we analyzed the attitude towards wealth and poverty of the Russian and Uzbek peoples.